Gender Risk and Femininity: Personal Political Branding of Female Politicians in the Strong Political Dynasty Feature of South Sulawesi - DEWI, KURNIAWATI HASTUTI (Jurnal Studi Pemerintahan, 2018)
Personal political branding becomes an important element in political contestation under the new direct democracy in Indonesia. In the male-dominated political atmosphere, it is interesting to analyze creation and development of personal political branding by female politicians. This paper explores stories of the two female politicians, each a candidate for the district head of Gowa (Tenri) and North Luwu (Indah) in the 2015 direct local election in South Sulawesi Province, where a strong political dynasty is the primary feature. This is qualitative research employing feminist research methodology by interviewing the two female politicians. This paper reveals that the use of femininity element in the tagline SAYANG IBU (love your mother) as Tenri’s personal political branding contains of what I call ‘gender risk’ which disadvantaged her. Within a strong political dynasty feature of South Sulawesi which is patriarchal, her opponent created a counter narrative to weaken her and pointed out centrality of a male politician. On the other hand, a successful female politician candidate for the district head of North Luwu, Indah, used PINTAR (smart) as her personal political branding which did not resemble her femininity and did not exclusively target women. By doing so, this paper offers different findings from those of the previous research which suggest that femininity can help all candidates to stand out. In a strong political dynasty feature, it is important to pay attention to the subconscious element such as patriarchal ideology which often plays or is used to weaken or against female politicians.